Desenvolvimento, aceitação e caracterização físico-química e sensorial de licor de banana - Jesus Filho, Milton de (2016)
The liquor is an alcoholic beverage that is characterized by high proportion of sugar, mixed with alcohol and with some aromatic principles, giving liqueurs flavored and distinctive flavors. The banana is a fruit that stands out in the state economy, may be an alternative for processing liqueurs due to its characteristic flavor and color, as well as being produced throughout the year, enabling the product to be supplied to the market on a regular basis. This study aimed to develop banana liquor and assess their acceptance, sensory profile, characterized as the physical and chemical analysis, investigate their aging, study the effect of clarifying and identify the main volatile compounds responsible for the banana aroma and banana liqueur. The work was divided into three phases. Initially, liqueurs were made by mixing water, syrup extract and refined sugar, in suitable proportions so that the liquor had alcohol and sugar content according to the desired formulation. In the first stage, a sensory acceptance was performed to investigate the effect of the alcohol content of the extraction solution on the color, aroma, flavor and overall impression of liqueurs. It used the desirability function to optimize the results found in this study, inferring on the optimal formulation. In the second stage, liqueurs were prepared using different amounts of alcohol and sugar, obtained by the Central Composite Rotational Design (CCRD). They were evaluated for pH, soluble solids, refractive index, density, absorption and colorimetric parameters. Also it was made a sensory analysis to judge the overall impression and the intention of purchasing the product. It was also applied to the desirability function in order to optimize multiple responses found. The best formulation obtained in the second stage was investigated during 60 days of storage, for pH, acidity, absorbance, turbidity, oxygen concentration in the headspace in addition to the acceptance regarding color, aroma, taste, overall impression and purchase intent. For clarification of the liquor, the effect filtration was studied of the paper filter and diatomaceous earth during storage. For sensorial characterization, we used the method Profile Description Optimized (PDO), and evaluated the attributes adhesion, viscosity, banana aroma, alcoholic aroma, alcoholic flavor and sweet taste, for 13 pre-selected judges. The analysis of volatile compounds carried in banana and banana liquor were made through the Microextration Solid phase (SPME) and injected into the GC/MS. The alcoholic content of the extraction solution influenced the taste and overall impression of banana liqueur, and the solution developed with 62,47 ºGL alcohol showed higher overall desirability. Liqueurs made with different amounts of alcohol and sugar differed in relation to soluble solids, refractive index, density, sensory acceptance and purchase intent. The formulation in which the optimal conditions were maximized, that was prepared with 17,29 ºGL alcohol and 289,89 g/L sugar. Aging influenced on physico-chemical characteristics, and to identify more acceptable and more likely to purchase liquor banana during storage. It was checked the influence of fining agents, and the storage time of the liquor, as the turbidity, absorbance, and L *. In the PDO, samples differed in adherence, alcoholic aroma, alcoholic flavor and sweet taste. Volatile compounds responsible for the characteristic aroma of banana and banana liquor have been identified. On banana esters were found, such as isoamyl acetate, butanoate isobutyl, butyl butyrate, isobutyrate, isoamyl butyrate, isoamyl, isovalerate, isoamyl butyrate, hexyl and hexanoate, isoamyl, while the liquor, the identified analytes were isobutyrate isoamyl butyrate, isoamyl, isoamyl isovalerate and isoamyl hexanoate.